PRIVILEGES OF QARDH FINANCING AT MICRO WAQF BANKS - Mohammad H Holle; Rosita Tehuayo; Magfirah Karanelan (Tasharruf: Journal Economics and Business of Islam, 2023)
Writing this article aims to reveal and prove the privilege of financing using a Qardh contract at the Micro Waqf Bank Al-Anshor Cares Ambon. The research method used is field research with a case study approach and a qualitative paradigm. Data collection techniques using observation and interviews focused on indicators of Qardh financing without collateral, Qardh without interest, channeling funds on target, group or cooperation systems, managed by Micro Waqf Banks formed by Islamic Boarding Schools, business coaching, and avoiding moneylenders, cooperation system (Gotong Royong) managed by Islamic boarding schools with permission from the OJK, providing business knowledge and training as well as religious education. The results of this study found that the qardh financing feature can change the daily life of micro-entrepreneurs, increase income, avoid loan sharks and interest on loans, better household consumption patterns, and relatively good family education. This proves that Qardh financing has advantages over other financing models.